2022
DOI: 10.1097/ta.0000000000003808
|View full text |Cite
|
Sign up to set email alerts
|

Early pneumonia diagnosis decreases ventilator-associated pneumonia rates in trauma population

Abstract: An early BAL protocol identified trauma patients with early pneumonia, a separate entity from ventilator-associated pneumonia. Patients were treated based on clinical signs. There was no difference in clinical outcomes but reported VAP rate decreased by 28%.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 24 publications
1
6
0
Order By: Relevance
“…The reduced consciousness also makes the ABI patients more susceptible for aspiration pneumonia, impaired mucus clearance and VAP than ICU patients without ABI [ 19 , 22 , 23 ]. In a recent large European cohort of about thousand patients with TBI, one out of five developed VAP after a median interval of 5 days (interquartile range 3–7 days, indicating that 75% of episodes occurred in the first week of MV) [ 24 ].…”
Section: Respiratory Challenges In Patients With Abimentioning
confidence: 99%
See 1 more Smart Citation
“…The reduced consciousness also makes the ABI patients more susceptible for aspiration pneumonia, impaired mucus clearance and VAP than ICU patients without ABI [ 19 , 22 , 23 ]. In a recent large European cohort of about thousand patients with TBI, one out of five developed VAP after a median interval of 5 days (interquartile range 3–7 days, indicating that 75% of episodes occurred in the first week of MV) [ 24 ].…”
Section: Respiratory Challenges In Patients With Abimentioning
confidence: 99%
“…In a recent large European cohort of about thousand patients with TBI, one out of five developed VAP after a median interval of 5 days (interquartile range 3–7 days, indicating that 75% of episodes occurred in the first week of MV) [ 24 ]. Systematic performance of bronchoalveolar lavage within 24 h after intubation of trauma patients showed that 80% of samples grew some microorganisms and 30% are suspect of early pneumonia [ 22 ].…”
Section: Respiratory Challenges In Patients With Abimentioning
confidence: 99%
“…Infections related to trauma often affect multiple organs and can manifest early, within the first four days. This holds true in trauma patients with contaminated wounds and fractures (18), early aspiration pneumonia in brain-injured patients (19), or superinfection of lung contusions (20). Some trauma patients may experience systemic inflammatory response syndrome (SIRS), while others may exhibit a compensatory anti-inflammatory response syndrome (CARS) (21), both leading to a modulated inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…Thank you to Drs. Ross, Ness, and Cocanour for their insightful comments regarding our article, “Early Pneumonia Diagnosis Decreases Ventilator-Associated Pneumonia Rates in Trauma Population.” 1 We agree that screening bronchoscopy with bronchoalveolar lavage (BAL), as with any screening test, opens the potential for overtreatment. Our protocol was developed with these concerns in mind, with patients needing to meet several thresholds to receive antibiotic treatment for their early pneumonia.…”
mentioning
confidence: 99%